Analysis of Regional Development Inequality in The District / City of Central Sulawesi Province in 2018-2022 - Putri Rahmadani; Muhtar Lutfi; Yunus Sading; S. Suparman; Andi Herman Jaya (Golden Ratio of Data in Summary, 2024)
Development inequality is an important issue that affects the society and economic stability of a region. This study aims to analyze regional development inequality in the districts/cities of Central Sulawesi Province during the 2018-2022 period. The analysis used is quantitative descriptive analysis using secondary data and the Williamson Index analysis method as a measuring tool to assess the level of inequality between regions. The data analyzed included Gross Regional Domestic Product (GRDP) in each district/city of Central Sulawesi Province. The results showed that the Williamson index calculation of the level of regional development inequality in Central Sulawesi Province was 0,97, which indicated a high level of inequality. However, in 2022 there was a decrease in the Williamson Index to 0,46. Nevertheless, the level of inequality between districts/municipalities in Central Sulawesi Province is still categorized as high. This decrease in the Williamson Index indicates an improvement in the distribution of development, but more intensive efforts are still needed to achieve a more effective development balance from the local and central government to reduce development inequality.